2017
DOI: 10.1039/c7ra06464k
|View full text |Cite
|
Sign up to set email alerts
|

Mono and double Mizoroki–Heck reaction of aryl halides with dialkyl vinylphosphonates using a reusable palladium catalyst under aqueous medium

Abstract: 2-Aryl or 2,2-diaryl vinylphosphonates can be selectively obtained by using aryl halides or dialkylvinylphosphonate as the limiting reagent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…The greenness of the reaction was showcased by an effective reuse of the residual aqueous solution for both the reported couplings (Scheme 8b). 58…”
Section: The Heck-mirozoki Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The greenness of the reaction was showcased by an effective reuse of the residual aqueous solution for both the reported couplings (Scheme 8b). 58…”
Section: The Heck-mirozoki Reactionmentioning
confidence: 99%
“…Different DESs have been screened to overcome the problem of the poor solubility of steroids in aqueous solutions. The addition of 6% (v/v) of ChCl/urea (1 : 2) boosted the dehydrogenation of cortisone acetate into prednisone acetate by Arthrobacter simplex, 117 whereas the mixture ChCl/Gly (1 : 2) was found to improve the 15α-hydroxylation of D-ethylgonendione (57) to the corresponding 15α-hydroxy-Dethylgonendione (58), mediated by Penicillium raistrickii. This is a key biotransformation in the industrial synthesis of Gestodene steroids (Scheme 21).…”
Section: Biocatalyzed Transformations In Aqueous Des Mixturesmentioning
confidence: 99%
“…In a precedent publication one of us described the utilization vinyl phosphonic esters in the Matsuda–Heck reaction . Synthetic protocols toward the synthesis of bis-arylated vinylphosphonates are scarce in literature, and all procedures have moderate yields and a limited range of accessible substrates. Quite recently Tsai et al reported the first synthesis of bis-arylated vinylphosphonates via Heck reaction using aryl iodides as electrophiles . When considering that the phosphonic ester moiety represents a functional group that is isosteric to ester functionalities in medicinal chemistry, the synthesis of bis-arylated vinylphosphonates should be an auspicious target.…”
Section: Resultsmentioning
confidence: 97%
“…18−23 Quite recently Tsai et al reported the first synthesis of bis-arylated vinylphosphonates via Heck reaction using aryl iodides as electrophiles. 24 When considering that the phosphonic ester moiety represents a functional group that is isosteric to ester functionalities in medicinal chemistry, the synthesis of bisarylated vinylphosphonates should be an auspicious target. The synthetic applicability of our new catalytic procedure using the Matsuda−Heck reaction could be extended to the facile synthesis of these compounds for the first time (Table 3).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation